WSIS round two, phase two African perspectives - Opoku-Mensah, Aida (Technical Centre for Agricultural and Rural Cooperation, 2005)
Aida Opoku-Mensah believes that the upcoming WSIS regional conference in Accra, Ghana, is important not just for ICT pundits and activists, but for all African development actors.